Patient experiences of internet-based enhanced cognitive behavior therapy for eating disorders - Anne-Charlotte Wiberg; Ata Ghaderi; Thomas Parling; Magdalena Jansson; Elisabeth Welch (Internet Interventions)
Background: Internet-based Cognitive Behavioral Therapy (ICBT) has shown promise in addressing the treatment gap for eating disorders (EDs), with evidence indicating moderate to large effect sizes. However, some individuals experience no improvement or deterioration in their condition, highlighting the need to understand both successful and unsuccessful outcomes. Aim: This study aimed to explore patients' experiences undergoing Internet-based guided self-help treatment based on Enhanced Cognitive Behavior Therapy (ICBT-E) for bulimia nervosa (BN) and binge eating disorder (BED), focusing on both those who benefited from the treatment and those who did not. Method: Sixteen participants with a diagnosis of full or subthreshold BN or BED, including eight non-responders and eight responders, participated in a semi-structured telephone interview. Data were analyzed using qualitative content analysis. Results: Responders strongly identified with the content, facilitating treatment implementation, while non-responders found the content less relevant to their symptoms. The treatment was overall perceived as time-consuming, but non-responders found it overwhelming and struggled with motivation and self-discipline. Non-responders preferred synchronous communication, while responders valued the flexibility of asynchronous contact. Overall, participants acknowledged the importance of ICBT-E, though non-responders felt it was not tailored to their specific needs. Conclusions: The study highlighted considerations for designing and implementing ICBT-E, including tailoring content to diverse patient symptoms, managing time demands, and considering motivation and self-discipline when assigning this treatment. While ICBT-E shows promise for the widespread dissemination of treatment for EDs, ongoing evaluation of progress during treatment and timely referral to alternative interventions for non-responders are crucial for optimizing outcomes.